Drive of parallel flows by turbulence and large-scale E × B transverse transport in divertor geometry. (6th February 2017) - Galassi, D.; Tamain, P.; Bufferand, H.; Ciraolo, G.; Ghendrih, Ph.; Baudoin, C.; Colin, C.; Fedorczak, N.; Nace, N.; Serre, E.
Abstract: The poloidal asymmetries of parallel flows in edge plasmas are investigated by the 3D fluid turbulence code TOKAM3X. A diverted COMPASS-like magnetic equilibrium is used for the simulations. The measurements and simulations of parallel Mach numbers are compared, and exhibit good qualitative agreement. Small-scale turbulent transport is observed to dominate near the low field side midplane, even though it co-exists with significant large-scale cross-field fluxes. Despite the turbulent nature of the plasma in the divertor region, simulations show the low effectiveness of turbulence for the cross-field transport towards the private flux region. Nevertheless, a complex pattern of fluxes associated with the average field components are found to cross the separatrix in the divertor region. Large-scale and small-scale turbulent E × B transport, along with the ∇ B drift, drive the asymmetries in parallel flows. A semi-analytical model based on mass and parallel momentum balances allows the poloidal drift effects on the asymmetry pattern to be evaluated. As in the experiments, a reversed B T simulation provides a way of self-consistently separating the effects of turbulent transport and large-scale flows, which must be reversed for a reversed field. The large-scale contribution is found to be responsible for typically 50% of the effect on the Mach number, evaluated at the top of the machine. The presented picture shows the complex interplay between drifts and turbulence, underlining the necessity of a global approach to edge plasma modelling, including a self-consistent description of the turbulence.